Deformation and fluid flow in the Huab Basin and Etendeka Plateau, NW Namibia - Salomon, Eric; Koehn, Daniel; Passchier, Cees; Chung, Peter; Haeger, Tobias; Salvona, Aron; Davis, Jennifer (Journal of Structural Geology, 2016)
The Lower Cretaceous Twyfelfontein sandstone formation in the Huab Basin in NW Namibia shows the effects of volcanic activity on a potential reservoir rock. The formation was covered by the Parana-Etendeka Large Igneous Province shortly before or during the onset of South-Atlantic rifting. Deformation bands found in the sandstone trend mostly parallel to the continental passive margin and must have formed during the extrusion of the overlying volcanic rocks, indicating that their formation is related to South-Atlantic rifting. 2D-image porosity analysis of deformation bands reveals significant porosity reduction from host rock to band of up to 70%. Cementation of the sandstone, linked to advective hydrothermal flow during volcanic activity, contributes an equal amount to porosity reduction from host rock to band when compared to initial grain crushing. Veins within the basaltic cover provide evidence for hot fluid percolation, indicated by spallation of wall rock and colloform quartz growth, and for a later low-temperature fluid circulation at low pressures indicated by stilbite growth sealing cavities. Sandstone samples and veins in the overlying volcanic rocks show that diagenesis of the Twyfelfontein sandstone is linked to Atlantic rifting and was affected by both hydrothermal and low-thermal fluid circulation. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Deformation bands; Cataclastic bands; syn-volcanic faulting; Quartz veins; Porosity analysis; South Atlantic rifting